ORGANIZING EXPERIMENTAL CREATIVE WORKSHOPS FOR SCHOOL STUDENTS BASED ON NATIONAL EMBROIDERY ART - Nematova Tursuntosh Alisher qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article analyzes the pedagogical, artistic, and creative aspects of organizing experimental workshops for school students based on national embroidery art. National embroidery is not only a decorative tool but also an effective means of developing students’ aesthetic taste, creative thinking, and cultural identity. The article explores how to integrate traditional embroidery patterns into workshop activities, select color schemes, and implement practical design projects. Research results show that such workshops play a crucial role in enhancing students’ artistic competencies, creativity, and understanding of national heritage.